2012
DOI: 10.7314/apjcp.2012.13.8.4097
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and Prostate Cancer Risk in Asian Countries: a Meta-analysis

Abstract: Background/Aims: Diabetes mellitus (DM) is widely considered to be associated with risk of cancer, but studies investigating the association between DM and prostate cancer in Asian countries have reported inconsistent findings. We examined this association by conducting a detailed meta-analysis of studies published on the subject. Methods: Cohort or case-control studies were identified by searching Pubmed, Embase and Wanfang databases through May 30, 2012. Pooled relative risk (RR) with its corresponding 95% c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 27 publications
4
37
2
2
Order By: Relevance
“…Many co-morbidities were associated with prostate cancer seen in higher age population. Our findings with low level (6.4%) co-morbidity with DM does not concordance with the present meta-analysis findings provide strong evidence that DM is associated with an increased risk of prostate cancer in Asians (Long et al, 2012) In relation to well-recognized impact of genetic risks on the development of disease, prostate cancer occurs often within a family, and the family history is an empirical indicator in prostate cancer diagnosis (Wang et al, 2011). Nonetheless, identification of positive family history for prostate cancer in first-degree relatives only in 4% of our patients is in line with the past reports indicating known susceptibility genes to be involved in only approximately 10% of cases despite a high heritability shown in twin studies (Auvinen et al, 2011).…”
Section: Discussioncontrasting
confidence: 66%
“…Many co-morbidities were associated with prostate cancer seen in higher age population. Our findings with low level (6.4%) co-morbidity with DM does not concordance with the present meta-analysis findings provide strong evidence that DM is associated with an increased risk of prostate cancer in Asians (Long et al, 2012) In relation to well-recognized impact of genetic risks on the development of disease, prostate cancer occurs often within a family, and the family history is an empirical indicator in prostate cancer diagnosis (Wang et al, 2011). Nonetheless, identification of positive family history for prostate cancer in first-degree relatives only in 4% of our patients is in line with the past reports indicating known susceptibility genes to be involved in only approximately 10% of cases despite a high heritability shown in twin studies (Auvinen et al, 2011).…”
Section: Discussioncontrasting
confidence: 66%
“…26 This discrepancy may be the result of confounding by BMI, which was not adjusted for, as well as a significant increase in the risk of prostate cancer in Asian populations compared to Western populations. A recent meta-analysis also seemed to confirm their findings of increased post-DM risk, 27 but suffered from poor quality data by including several studies that relied on self-report to determine DM status, as well as studies with minimal adjustment for confounding. Additionally, the latter meta-analysis did not distinguish between odds ratios, HRs, and RRs for pooling, possibly resulting in considerable bias.…”
Section: Discussionmentioning
confidence: 84%
“…An inverse association of diabetes with prostatic cancer has been noted in several studies, which may be due to reduced testosterone levels in diabetes, altered insulin and leptin concentrations, statins and metformin use, and changes in diet and lifestyle in controlling diabetes (Kasper and Giovannucci, 2006;Avci et al, 2013;Fall et al, 2013;Demir et al, 2014). Several studies have reported decreased PCa risk among those with DM, and others found either no protective effect or even an elevated risk (Bonovas et al, 2004;Gong et al, 2006;Leitzmann et al, 2008;Hong et al, 2011;Wu et al, 2011;Long et al, 2012 lower risk of developing prostate cancer. In addition, the mechanism through which DM and prostate cancer are related has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%